Atom probe tomography today - Cerezo, A; Clifton, P; Galtrey, M; Humphreys, C; Kelly, T; Larson, D; Lozano-Perez, S; Marquis, E; Oliver, R; Sha, G; Thompson, K; Zandbergen, M; et al. (Elsevier, 2007)
This review aims to describe and illustrate the advances in the application of atom probe tomography that have been made possible by recent developments, particularly in specimen preparation techniques (using dual-beam focused-ion beam instruments) but also of the more routine use of laser pulsing. The combination of these two developments now permits atomic-scale investigation of site-specific regions within engineering alloys (e.g. at grain boundaries and in the vicinity of cracks) and also the atomic-level characterization of interfaces in multilayers, oxide films, and semiconductor materials and devices. © 2007 Elsevier Ltd. All rights reserved.